Risk of secondhand smoke exposure and severity of COVID-19 infection: multicenter case–control study - Kishore, Surekha; Shah, Vandana; Bera, Om Prakash; Venkatesh, U.; Kakkar, Rakesh; Aggarwal, Pradeep; Bhardwaj, Pankaj; Singh, C. M.; Maliye, Chetna; Garg, Suneela; Menon, Geetha R.; Misra, Puneet; et al. (Frontiers in Public Health, 2023)
role of SHS. Therefore, this study was done to determine whether SHS is an independent risk factor for COVID-19 infection, severity, mortality, and other co-morbidities. Methodology: Multicentric case-control study was conducted across six states in India. Severe COVID-19 patients were our cases, and mild and moderate COVID-19 as control were evaluated for exposure of SHS exposure. The sample size was calculated using Epi-info version 7. A neighbourhoodmatching technique was utilised to address ecological variability and enhance comparability between cases and controls, considering age and sex as additional matching criteria. The binary logistic regression model was used to measure the association, and results were presented using an adjusted odds ratio. The data was analysed using SPSS version 24 (SPSS Inc., Chicago, IL, USA).Results: A total of 672 cases of severe COVID-19 and 681 controls of mild and moderate COVID-19 were recruited in this study. The adjusted odds ratio (AOR) for SHS exposure at home was 3.03 (CI 95%: 2.29-4.02) compared to mild/moderate COVID-19, while SHS exposure at the workplace had odds of 2.19 (CI 95%: 1.43-3.35). Other factors significantly related to the severity of COVID-19 were a history of COVID-19 vaccination before illness, body mass index (BMI), and attached kitchen at home. Discussion: The results of this study suggest that cumulative exposure to secondhand cigarette smoke is an independent risk factor for severe COVID-19 illness. More studies with the use of biomarkers and quantification of secondhand smoke exposure in the future are needed.